Kurangnya Komunikasi Antardepartemen dalam Perusahaan Manufaktur dan Dampaknya terhadap Kinerja Organisasi - Sinta Rahmawati (GLOBAL SCIENTS PUBLISHER, 2025)
The lack of inter-departmental communication in the manufacturing industry is a critical issue that affects production efficiency, product quality, and operational costs. This study examines four real cases caused by miscommunication between the Production, PPIC (Production Planning and Inventory Control), and Engineering departments, namely: (1) failure in design change integration, (2) misalignment between planning and capacity, (3) procedural errors, and (4) failure in information system integration. The research method employs a literature review of accredited journals (2016–2021) and company case studies. The findings identify recurring issues such as information asymmetry, weak coordination procedures, fragmented information systems, and silo mentality. Recommended solutions include technological implementations (integrated ERP/APS systems), collaborative procedures (daily meetings, ECO), and human resource training (cross-departmental communication). These findings underscore that system integration, standardized procedures, and a collaborative culture are key to enhancing organizational performance.